Cave paintings - Buitrago, Jairo (Groundwood Books, House of Anansi Press, 2020)
"Our hero travels all alone on a spaceship, through the universe, past galaxies, comets and planets to go visit his grandmother on Earth for the summer holidays. She takes him to visit an ancient cave, where he discovers handprints and drawings of unknown animals made by human beings just like him. To top off his wonderful holiday she gives him mysterious objects that once belonged to his grandfather -- paper and crayons."--
Translation from the Spanish of: Las pinturas rupestres
Keywords: Reise; Raumfahrt; Großmutter; Weltraum; Zeichnung; Junge; Besuch; Vergänglichkeit; Erde; Grandparents / Juvenile fiction; Interplanetary voyages / Juvenile fiction; Cave paintings / Juvenile fiction; Colored pencils / Fiction; Grands-parents / Romans, nouvelles, etc. pour la jeunesse; Voyages interplanétaires / Romans, nouvelles, etc. pour la jeunesse; Livres d'images pour enfants; Bilderbuch